Integrated marketing communication effectiveness valuation approaches: bibliometric analysis of recent years - A.Zh. Orazayev; V.S. Garkavenko (Хабаршысы. Экономика сериясы)
Integrated Marketing Communication (IMC) has emerged as a core element of strategic marketing, particularly in the context of digital transformation and increasing demands for accountability. Despite its centrality in practice, scholarly evaluation of IMC effectiveness remains methodologically diverse and theoretically fragmented. This study aims to systematically analyze how IMC effectiveness has been assessed in peer-reviewed academic literature over the past 34 years (1991–2024). The research seeks to identify dominant theoretical perspectives, categorize key measurement tools, and expose gaps in standardization. To achieve these objectives, a bibliometric analysis was conducted using the Bibliometrix R package. The dataset comprised 410 peer-reviewed articles retrieved from the Scopus database through a structured query focused on IMC effectiveness. The methodology included keyword co-occurrence analysis, co-citation mapping, and trend analysis to reveal thematic clusters, leading contributors, and the intellectual structure of the field. The results identified five major thematic clusters: (1) conceptual foundations, (2) brand equity and consumer behavior, (3) measurement models and return on investment, (4) digital and social media integration, and (5) global and emerging market applications. The findings reveal a progression from conceptual discourse in the 1990s to the emergence of quantitative models and digital engagement frameworks in recent years. Despite this development, a unified evaluation framework remains absent. This study contributes to the advancement of IMC scholarship by synthesizing key trends and offering a foundation for future interdisciplinary research. Practically, the findings underscore the need for context-sensitive, integrative metrics to guide both academic inquiry and managerial decision-making.